Application of bacterin to control luminescent Vibrio harveyi infection in hatchery reared Syclla serrata larvae - Zafran (College of Fisheries and Ocean Sciences, U. P. in the Visayas, 2001)
A series of experiments were conducted to evaluate the pathogenicity of luminescent Vibrio harveyi to different zoeal stages of Scylla serrate and effectiveness of Vibrio harveyibacterin against Vibrio harveyi infection in Scylla serrate larvae. Results of pathogenicity tests indicated that all of five zoeal stages of Scylla serrate were susceptible to Vibrio harveyi infection. Zoea-I and Zoea-2 were the most susceptible stages. Scylla serrate larvae gave psotive response to Vibrio harveyibacterin vaccination. The optimum duration of immersion of S. serrate larvae in bacterin solution was 1-3 h. Survival rates of vaccinated groups were higher than htose of unvaccinated groups following challenge with live Vibrio harveyi. Protection against Vibrio harveyi infection given by bacterin vaccination still persisted at least until the larvae reached Zoea-5 stage or at least for 11 days post vaccination as shown by challenge test results. Since this study was conducted under laboratory conditions, it is suggested that evaluation of the effectiveness of Vibrio harveyibacterin to control luminescent Vibrioharveyi infection in Scylla serrate larvae be further conducted under hatchery conditions by comparing the survival of vaccinated and unvaccinated crab larvae in a larger scale.